Implantación de un sistema contable en el Comercial Johanna, de la ciudad de Yantzaza, provincia de Zamora Chinchipe, periodo noviembre - diciembre del 2015. - Urgiles Torres, Tatiana Maribel (2018)
This work is justified through the application of an accounting system, which represents a favorable solution that allows your property to make timely decisions about your economic reality, promoting business growth; in addition to fulfilling a fundamental requirement, prior to obtaining the Degree in Accounting and Audit Engineering, Public Accountant Auditor, CPA. Thus, the application of an Accounting System in the "COMERCIAL JOHANNA" represents a viable solution that allows access to the financial situation of the business, through the use of accounting methods from the collection of support information, the structure of the Plan and the Accounts Manual, Initial Inventory, Initial Situation Statement, Daily Book, General Ledger, Checking Balance, Worksheet and Financial Statements, thus demonstrating the Loss generated during the period applied; its implementation helped to fulfill the objectives set. Based on the results obtained, it was concluded that the application of an accounting process in the market has been made through real data about its operations; reflected in the Financial Statements framed in the Accepted Accounting Principles and the International Accounting Standards; so it is recommended that your property implement accounting as a means to visualize your current financial position, and in this way, help the application of corrective measures that contribute to the economic and financial development of the business.